The impact of sociodemographic and health aspects on cognitive performance in the older adult population in the republic of Serbia - Mirkovic, Andrea; Radevic, Svetlana; Radovanovic, Snezana; Simic Vukomanovic, Ivana; Janicijevic, Katarina; Ilic, Sanja; Djordjevic, Ognjen; Djordjevic, Gordana; Radovanovic, Jovana; Selakovic, Viktor; Savic, Nikola; Gogic, Andjela (Frontiers in Public Health, 2024)
The aim of this study was to investigate how sociodemographic and health factors contribute cognitive abilities in the older population of the Republic of Serbia, using data from the 2019 national health survey. The study included 3,743 participants, of whom 2,061 (55.1%) were women and 1,682 (44.9%) were men. The median age of all participants was 72 (10) years. Study used logistic regression on cross-sectional data to analyze how education, social support, and healthcare access affect cognitive abilities, while adjusting for demographic variables.The results revealed negative associations between higher levels of education and lower odds of experiencing memory and concentration problems, while recent visits to specialists were positively associated with increased risk for the same. The highest percentage of participants (22.6%) reporting major difficulties in memory and concentration were in the age group of 85-89 years (p<0.001). A statistically significant relationship was found between social support and issues related to memory and concentration (p < 0.001). Social support emerged as a significant factor in preserving cognitive abilities. The discussion underscores the need for a comprehensive approach in promoting cognitive health, taking into account education, social integration, and access to healthcare as key factors. The study acknowledges its limitations, including its cross-sectional nature and potential subjective biases in self-assessment of cognitive abilities. Future research should incorporate longitudinal studies and more objective measures of cognitive abilities.